Biochar regulates bacterial-fungal diversity and associated enzymatic activity during sheep manure composting. (February 2022) - Duan, Yumin; Awasthi, Mukesh Kumar; Wu, Huanhuan; Yang, Jianfeng; Li, Zelin; Ni, Xinhua; Zhang, Jiatao; Zhang, Zengqiang; Li, Huike
Graphical abstract: Highlights: Impact of biochar amendment on microbial dynamics and enzymatic activities was studied. Most enzymatic activity enhanced after biochar amendment in composting feedstock. Biochar enriched bacterial diversity and decreased fungal diversity. The most key microbial connectors affiliated to Oligella and Fermentimonas . More complex correlation between enzyme and bacterial compared to fungal community. Abstract: Aimed to evaluate the coexistence of bacterial and fungal diversity and their correlation with enzymatic activity in response to biochar. This study performed aerobic composting based on typical agricultural wastes of sheep manure with additive apple tree branch biochar at distinct concentration (0, 2.5, 5, 7.5, 10 and 12.5% corresponding from T1 to T6). The result demonstrated that appropriate amendment of biochar enriched bacterial diversity (1646–1686 OTUs) but interestingly decreased fungal diversity (542–630 OTUs) compared to control (1444 and 682 OTUs). Biochar addition enhanced all enzymatic activities and its correlation with bacterial was more complex than fungal community (786 and 359 connect edges). The dominant microbes comprised of Firmicutes (45.2–35.2%), Proteobacteria (14.0–17.5%), Basidiomycota (32.4–49.5%) and Ascomycota (11.3–37.5%) among all the treatments. Overall, biochar regulates the composting microenvironment by influencing the microbial diversity and associated enzymatic activities.